STUDY CURRENT STATUS OF TDS DISTRIBUTION IN THE PLEISTOCENE AQUIFER IN COASTAL ZONE OF NAM DINH PROVINCE - Thu, Trinh Hoai; Trung, Nguyen Nhu; Thang, Do Van; Manh, Vu Van; Hang, Nguyen Thu (Vietnam Journal of Marine Science and Technology, 2016)
Saltwater intrusion has occurred in coastal aquifers in Nam Dinh province, Vietnam, which causes many negative effects on economic activities and especially residential life. Determining fresh-saltwater distribution is therefore necessary for authorities to have fundament to release policies and solutions promptly to prevent this issue. Based on the analysis of samples, 3 regression equations of each couple of the conductivity, total dissolved solids (TDS) and chloride concentration were formulated and displayed on graphs, these can be applied to calculate TDS from available conductivity or chloride concentration values in any areas. Calculating all input data, a variogram was created, which indicates the spatial correlation between points. Then, Kriging interpolation was applied in map-making process. Finally the spatial distribution of fresh and saltwater was delineated. Freshwater regions are located in the southern part and a small area in the north of Nam Dinh province.